Transcription Aesthetics - Keith M. Murphy (Semiotic Review)
I start with a premise that you may disagree with: a lot of the transcripts that discourse analysts publish are bad. I explain that what I mean by this, and then propose a solution: let’s make published transcripts good, in the hopes of devising new possibilities for growing discourse analytic knowledge. I offer four provisional and interrelated principles that I argue are critical for developing a new kind of transcription aesthetics, along with some ideas and examples for how to employ them. The first principle sets the stage for those that follow: treat transcription not as a “word process” that produces written-text artifacts, but a graphic process that produces images. The second is to work compositionally, approaching each aspect of the transcript as worthy of its own specific kinds of attention. The third principle is to think openly about order when designing a transcript; and the fourth principle is to prioritize intelligibility. In the end and along the way, I make some arguments for why reformulating transcribing as a design process can help advance discourse analytic practice and theory.